Using 3D Media to Improve Short Stories Writing Skill on Junior High School Students - Khaerunnisa; Mutiarani; Wika Soviana Devi (Journal of Physics: Conference Series, 2023)
The writers conducted this research as the result of field observation that found the students’ short stories writing skill are still poor. The purpose of this research is to improve short stories writing skill through three dimensional media of the students in the class IX SMPLB A Tan Miyat, Bekasi, West Java. The research method used in this research is Classroom Action Research method. This research was conducted for two months December to January for two cycles and in each cycle held in two meetings. Learning activities in short stories writing using three-dimensional media is expected that students will be easier to develop creativity and imagination in making a short story. The results of this study show that using three-dimensional media can improve the ability to write short stories. This findings of the research are the data obtained during pre-cycle is only 30%. After implementing the three dimensional media towards write short stories writing, the students’ short stories writing skill have increased. In the first cycle, the students’ short stories writing increased 50%, and on the second cycle improved into to 95%. The increasing of the students’ short stories writing skill will also improve the quality of language learning especially in the creative writing skill.